Educação integral no Ensino Médio e justiça curricular: protagonismo juvenil em Escola de Ensino Médio da Rede Pública Estadual de São Paulo participante do Programa Ensino Integral - Silva, Antonio Torquato da (2022)
This research analyzes the High School crisis from its symptoms of high dropout and failure rates, culminating in lack of opportunities, perspectives, and various types of injustices. The objective is to critically analyze the effectiveness of High School in the education of adolescents and young people who are autonomous, reflective, critical, building their identities, conscious and practicing of their duties and rights, reflecting on educational policies and actively positioning themselves before them, being protagonists of their own story and enabling them to access and remain in higher education if they so desire. The hypothesis of this research is that high school can (and therefore must) promote Curricular Justice through the "Integral Education" of adolescents and young people. This research assumes that Integral Education is an inalienable subjective public right. To this end, in the construction of data, bibliographic and documentary researches, and a field incursion in a public school in São Paulo participating in the Integral Education Program to interview high school students, adopting a qualitative approach based on the dynamic relationship between the real world and the subjects, were developed. The collected data were organized, systematized and grouped into categories using Content Analysis procedures. From the analysis of the data obtained and as a result of this trajectory, it was conclusively observed that the legislation on high school is not known by the students, that the obligatoriness of high school is not yet universalized to all young people, much less at the right age, that schools do not know their students with propriety, that the participation of students is limited and insufficient, and that all of this requires an active listening in relation to the students and public policies of expansion of Integral Education programs, with full-time study